P760 Adalimumab biosimilars versus Azathioprine: indirect comparison of efficacy, safety and persistence in treatment. (30th January 2023) - Saladino, M; Celsa, C; Amato, L M; Di Giorgio, F M; Muscarella, S; Melatti, P; Brinch, D; Cappello, M
Abstract: Background: The advent of low-cost adalimumab (ADA) biosimilars is expected to increase access to biologics. Whether ADA biosimilars influence the use of conventional immunomodulators, especially azathioprine (AZA), which should be the alternative in steroid-dependant IBD, has not been investigated and comparative data on efficacy and safety are scanty. The aim of this study is to compare ADA biosimilars and Azathioprine (AZA) in patients with IBD naive to biologics and/or immunosuppressive agents. Methods: A retrospective-prospective observational study was conducted on 55 consecutive IBD-patients (30 CD, 25 UC), in follow up in our tertiary referral center, who started ADA biosimilars or AZA between 11/2018 and 11/2021. Drug choice was upon clinical judgement. Primary outcomes, clinical response and steroid-free clinical remission, were evaluated at 12 and 84 weeks, using HBI for CD and p-Mayo score for UC. Active disease was defined HBI>5 for CD e p-Mayo>2 for UC. Secondary outcomes were persistence and retention rate. Results: The two treatment groups showed similar baseline characteristics regarding age, sex, familial predisposition, smoking, type of IBD and previous surgery, except the use of systemic steroids (42, 85% of patients treated with ADA and 18, 5% of patients with AZA; p= 0, 029) and presence of active disease (60, 71 % of ADA and 37, 03% of AZA; p=0, 082). At week 12 clinical response was obtained in 22/28 (78, 6%) treated with ADA and in 22/27 (81, 5%) with AZA (p=0.789), at week 84 response rate was obtained in 10/10 (100%) of ADA e 10/13 (76, 9%) of AZA (p= 0, 155). Clinical remission at week 12 was achieved by 19/28 (67, 9%) of ADA patients and by 24/27 (88, 9%) AZA (p=0, 061), at week 84 by 10/10 (100%) of ADA and by 12/13 (92, 3%) of AZA (p=0, 380). No adverse events were registered in the ADA group, 5 AE leading to discontinuation occurred in the AZA group (0% VS 18, 52%, p=0, 018). The retention rate was 85, 7% for ADA and 74, 1% and AZA (p= 0, 285). According to IBD type, treatment persistence of ADA was higher in patients with CD (Log-rank test p=0, 004); in CD the persistence rate is significantly better for ADA as compared to AZA. (Log-rank test p=0, 008), in UC the difference was not significant (p=0, 41). Conclusion: Our results suggest that ADA biosimilars are an effective therapy in steroid-dependent IBD, with a better safety profile compared to AZA, thus resulting in a higher probability of treament persistence especially in CD. The use of AZA is expected to decline in the next years.